2021
DOI: 10.1002/srin.202100238
|View full text |Cite
|
Sign up to set email alerts
|

Microstructure and Mechanical Properties of Wire + Arc Additively Manufactured Mild Steel by Welding with Trailing Hammer Peening

Abstract: The microstructure of the parts manufactured by Wire Arc Additive Manufacture (WAAM) is dominated by columnar grains with large size, [1][2][3][4][5] which seriously affects the service performance and life of the parts. [2,[5][6][7] There are two kinds of viable approaches to improve the microstructure of the welds produced by Additive Manufacturing (AM): adjusting the welding process parameters [8][9][10][11][12][13] and introducing external auxiliary means. [14][15][16][17][18][19][20][21] The formation of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 35 publications
(50 reference statements)
0
1
0
Order By: Relevance
“…Xiong et al [110], low-alloy steel (AWS ER70S-6) DEDed-laser + interlayer hot hammer peening, also observed the parent phase (γ) dynamic recrystallization at the layer surface; however, due to the γ → α transformation, the final microstructure is not significantly affected. Although the prior γ grain size affects material hardenability and α formation/morphology, the mandatory effect on the final microstructure is governed by the cooling rates [165], which is almost insensible to the interlayer hot hammer (low effect on geometric aspects of the deposited layer) [110]. Thus, the interlayer hot hammer peening for transformable alloys showed insufficient grain refinement that justified its use.…”
Section: Transformable Solid-state Alloysmentioning
confidence: 95%
See 1 more Smart Citation
“…Xiong et al [110], low-alloy steel (AWS ER70S-6) DEDed-laser + interlayer hot hammer peening, also observed the parent phase (γ) dynamic recrystallization at the layer surface; however, due to the γ → α transformation, the final microstructure is not significantly affected. Although the prior γ grain size affects material hardenability and α formation/morphology, the mandatory effect on the final microstructure is governed by the cooling rates [165], which is almost insensible to the interlayer hot hammer (low effect on geometric aspects of the deposited layer) [110]. Thus, the interlayer hot hammer peening for transformable alloys showed insufficient grain refinement that justified its use.…”
Section: Transformable Solid-state Alloysmentioning
confidence: 95%
“…Ye et al [108] (DED-laser) and Li et al [109] (DEDlaser) developed a hot ultrasonic micro-forging system with an operating frequency of 20 kHz; Xiong et al [110] (DEDarc), a hot hammer penning system with an operating frequency of 21 Hz. These systems [108][109][110] (Fig. 12) resemble the cold hammer previously shown in Fig.…”
Section: Hammering Peening and Forgingmentioning
confidence: 99%
“…The horizontal tensile property is the best when the interlayer is hammered three times. Xiong 17 found that hammering can improve the mechanical properties of the near-surface layer of the mild steel weld and improve the strength of the weld in the study of wire+arc additively manufactured mild steel by welding with trailing hammer peening. Zou 18 demonstrated by finite element simulations that hammering could effectively reduce residual stress in welds.…”
Section: Introductionmentioning
confidence: 99%
“…Average tensile properties of WAAM ER70S-6 reported in literature[12][13][14][15][16][17][18][19][20][21][22][23][24][25][26][27][28][29][30][35][36][37][38][39][40][41][42]44,45].…”
mentioning
confidence: 99%